2021
DOI: 10.1016/j.jpha.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and mode of action of terpene linalyl anthranilate against carbapenemase-producing Klebsiella pneumoniae

Abstract: Mining of plant-derived antimicrobials is the major focus at current to counter antibiotic resistance. This study was conducted to characterize the antimicrobial activity and mode of action of linalyl anthranilate (LNA) against carbapenemase-producing Klebsiella pneumoniae (KPC-KP). LNA alone exhibited bactericidal activity at 2.5% ( V/V ), and in combination with meropenem (MPM) at 1.25% ( V/V ). Comparative proteomic analysis showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…These ROS could initiate lipid oxidation via a membrane lipid attack and could thus disrupt bacterial cell membrane and hence leak intracellular contents. The ROS could also leak into intracellular regions and degrade nucleic acids, lipids, and/or proteins [ 34 ]. The presence of sesquiterpenes may also contribute to the antimicrobial activity of essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…These ROS could initiate lipid oxidation via a membrane lipid attack and could thus disrupt bacterial cell membrane and hence leak intracellular contents. The ROS could also leak into intracellular regions and degrade nucleic acids, lipids, and/or proteins [ 34 ]. The presence of sesquiterpenes may also contribute to the antimicrobial activity of essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the increase to the intracellular MDA content of V. vulnificus treated with OEO was consistent with the increased trend of ROS (Figure 6). Similarly, Yang et al [47] found that the quantitative MDA level of Carbapenemase-producing Klebsiella pneumoniae treated by linalyl anthranilate was significantly higher than those of untreated cells, and this trend was also found in the change of the ROS level. Moreover, Ajiboye et al [49] considered that the increase of MDA in catechin treated E. coli, Pseudomonas aeruginosa and Staphylococcus aureus indicates that the cells are attacked by macromolecules, which may have been due to lipid peroxidation caused by enhanced production of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, Li et al [46] found that epigallocatechin gallate, the main polyphenol component in tea, killed V. mimicus by increasing the production of intracellular ROS. Likewise, limonene can induce a large number of hydroxyl radicals, thereby improving the level of ROS in Penicillium digitatum spores [47]. Vatansever et al [44] believe that excessive ROS will destroy the defense systems of superoxide dismutase (SOD) and catalase (CAT) in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably the first huge-scaled study focusing on the beneficial effects of LEO when used in combination with other antimicrobial agents [114]. Another study conducted by Yang et al (2020) detected the presence of synergistic antimicrobial effects when LEOs are used concurrently with meropenem against carbapenemase-producing K. pneumoniae, where MIC values of both LEO and meropenem were found to be remarkably decreased. Checkerboard and time-kill assays revealed the FICI to be 0.31 and further proteomic analysis revealed the combination of LEO and meropenem causes disruption of the cellular membrane of K. pneumoniae via induction of oxidative stress, resulting in influx of LEO-meropenem and other generated free radicals into the bacterial cell [115].…”
Section: Leo and Antimicrobial Agentsmentioning
confidence: 81%